Quality Improvement And Product Development Of Banana Chips. Case Study In Ukm Keripik Pisang Se Maju Jaya Bumiayu, Malang. - Nur Istianah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2019)
Bumiayu is one of the villages that has a community that is active in running Small and Medium Enterprises (UKM), one of which is UKM SE. Maju Jaya Banana Chips. This UKM has a problem of having a short shelf life because the oil draining is not optimal. In addition, the product of banana chips are limited to only salted banana chips and dry sale chips. Thus a spinner is needed to optimize the copying process and also product innovations such as chocolate, caramel and balado banana chips. Extension activities and demonstrations on the manufacture of various flavored chips and grinder machines are expected to help increase the income of these SE Maju Jaya. The target in this community service program is the presence of new products from SE Maju Jaya Banana Chips and prolong the self life of their product.